Fixation of a Periprosthetic Intertrochanteric Hip Fracture below a Birmingham Hip Resurfacing - J. Macdonald; A. Robinson; I. Brown (Case Reports in Orthopedics)
This case report involves a 56-year-old female (Mrs X) with a traumatic intertrochanteric hip fracture with subtrochanteric extension below a previous Birmingham hip resurfacing. Periprosthetic fractures following hip resurfacing are usually subcapital and treated with a revision or conservative management. We present an unusual surgical problem with an interesting solution stabilising the fracture using a proximal femoral locking compression plate (LCP). Eight months following surgery the patient is able to walk pain free and there is good fixation and stability.